Evaluation of the Effect of Empowerment Model on Self-Efficacy and Self-Esteem among Diabetic Patients: A Randomized Control Trial Study - Ebrahimi 1, Hossein; Sadeghi 2*, Mahdi; Amanpour 3, Farzaneh; Fahidi 2, Fereshteh (Shahroud Journal of Medical Sciences, 2017)
Background: Improvement and enhancement level of psychological aspects of patients is important in the control of chronic diseases, especially in diabetes. This study aimed to determine the influence of empowerment model on self-efficacy and self-esteem in patients with diabetes.Methods: This study was a clinical trial comprising 103 patients with diabetes, which were randomly divided into experimental and control groups. Empowerment model was considered for the experimental group and routine education was considered for the control group. Applied research tools consisted of demographic data, standardized questionnaire of self-efficacy, and Coppersmith’s self- esteem questionnaire. Results: Before intervention,the two groups were not significantly different in the demographic variables, self-efficacy, and self-esteem scores. There was a significant difference between self-efficacy and self-esteem mean scores of patients, after intervention of the experimental group. Moreover, by using the paired t-test, before and after the intervention, the difference in mean scores of the experimental group was significant.Conclusions: Based on the obtained results, empowerment model has been effective on self-efficacy and self-esteem of diabetes patients. Therefore, empowerment based education planning for diabetic patients is recommended.